Absorption coefficient (ABSCO) tables for the Orbiting Carbon Observatories: Version 5.1. (November 2020) - Payne, Vivienne H.; Drouin, Brian J.; Oyafuso, Fabiano; Kuai, Le; Fisher, Brendan M.; Sung, Keeyoon; Nemchick, Deacon; Crawford, Timothy J.; Smyth, Mike; Crisp, David; Adkins, Erin; Hodges, Joseph T.; et al.
Highlights: Absorption coefficients for the Orbiting Carbon Observatory missions updated to v5.1 for the B10 Level 2 algorithm. Improved spectroscopy for Oxygen A-band results in reduced spatial variability in surface pressure retrieval bias. Orbiting Carbon Observatory retrievals are sensitive to changes to the water vapor continuum model. Abstract: The accuracy of atmospheric trace gas retrievals depends directly on the accuracy of the molecular absorption model used within the retrieval algorithm. For remote sensing of well-mixed gases, such as carbon dioxide (CO2 ), where the atmospheric variability is small compared to the background, the quality of the molecular absorption model is key. Recent updates to oxygen (O2 ) absorption coefficients (ABSCO) for the 0.76 µm A-band and the water vapor (H2 O) continuum model within the 1.6 µm and 2.06 µm CO2 bands used within the Orbiting Carbon Observatory (OCO-2 and OCO-3) algorithm are described here. Updates in the O2 A-band involve the inclusion of new laboratory measurements within multispectrum fits to improve relative consistency between O2 line shapes and collision-induced absorption (CIA). The H2 O continuum model has been updated to MT _ CKD v3.2, which has benefited from information from a range of laboratory studies relative to the model utilized in the previous ABSCO version. Impacts of these spectroscopy updates have been evaluated against ground-based atmospheric spectra from the Total Carbon Column Observing Network (TCCON) and within the framework of the OCO-2 algorithm, using OCO-2 soundings covering a range of atmospheric and surface conditions. The updated absorption coefficients (ABSCO version 5.1) are found to offer improved fitting residuals and reduced biases in retrieved surface pressure relative to the previous version (ABSCO v5.0) used within B8 and B9 of the OCO-2 retrieval algorithm and have been adopted for the OCO B10 Level 2 algorithm.